Perlindungan Hak Anak dalam Pasal 425 KUHP 2023: Analisis Klasifikasi Delik, Mekanisme Perlindungan, dan Tanggung Jawab Negara - Adhelia Ainur Safira; Rochmad Dwi Riwayanto (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to comprehensively analyze Article 425 of the 2023 Criminal Code concerning the protection of children from exploitation through three main aspects: classification of offenses, legal liability, and protection mechanisms. Through a normative juridical approach, it is argued that Article 425 of the 2023 Criminal Code is a regular offense that can be prosecuted without a complaint from the victim, based on the legal argument that Article 425 of the Criminal Code protects the public interest and that the victims in this case are children under the age of 12 who are unable to defend and uphold their legal rights. Classification as a regular offense also gives proactive authority to law enforcement officials and other institutions, such as social services and the UUPA, to follow up on cases of child exploitation without relying on reports, thereby strengthening law enforcement and the protection of children's rights. Law enforcement against perpetrators of exploitation is also important, accompanied by rehabilitation mechanisms for victims, in accordance with the principle of the best interests of the child as stipulated in the Convention on the Rights of the Child (CRC) and Law No. 35 of 2014 on Child Protection. This study also shows that harmonization of regulations is needed, both vertically and horizontally, to prevent conflicts between norms and legal loopholes. Thus, it is hoped that Article 425 of the 2023 Criminal Code can be implemented and successfully serve as a legal basis to ensure protection, justice, and welfare for children as the nation's future generation.